The SQ3R Method for Enhancing Reading Comprehension Among 8th-Grade Students at SMP Islam Insan Kamil Wonoayu - Jalil, Abdul (English Language and Literature in Education Journal, 2024)
Despite the acknowledged importance of effective reading comprehension strategies, specific challenges persist in enhancing students’ understanding, particularly in analytical texts. This study aimed to address these challenges by evaluating the impact of the SQ3R (Survey, Question, Read, Recite, Review) method on 8th-grade students’ reading comprehension at SMP Islam Insan Kamil Wonoayu. Using a classroom action research design, the study demonstrated that the SQ3R method led to a substantial improvement in students’ ability to comprehend analytical texts. By the second cycle, 83.3% of students showed notable progress, indicating the method’s effectiveness in addressing issues such as limited vocabulary and weak analytical skills. Nonetheless, the study uncovered several limitations, including the SQ3R method's restricted application to different student levels and text types, as well as insufficient exploration of its effectiveness across diverse genres. To remedy these issues, the study recommends integrating the SQ3R method more comprehensively into teaching practices, enhancing vocabulary instruction through targeted discussions and assessments, and fostering collaborative learning environments to boost student independence. Future research should explore the SQ3R method’s applicability across a broader range of student demographics and text genres, including both analytical and hortatory exposition texts, to gain a deeper understanding of its adaptability and effectiveness in varied educational settings.